Electrostatic layer-by-layer construction and characterization of photoelectrochemical solar cells based on water soluble polythiophenes and carbon nanotubes - Sgobba, Vito; Troeger, Anna; Cagnoli, Rita; Mateo-Alonso, Aurelio; Prato, Maurizio; Parenti, Francesca; Mucci, Adele; Schenetti, Luisa; Guldi, Dirk Michael (Journal of Materials Chemistry, 2009)
Positively and negatively charged functionalized polythiophenes and single walled carbon nanotubes were sequentially adsorbed on indium tin oxide electrodes by electrostatic and van der Waals interactions using the layer-by-layer deposition method. The resulting donor/acceptor photoelectrodes were tested as photoelectrochemical cells. Upon illumination, monochromatic incident photoconversion efficiencies of 8.2 and 4.3% were determined for eight stacks of single walled carbon nanotubes with ammonium and sulfonate polythiophene derivatives, respectively. © The Royal Society of Chemistry 2009.